Pengalaman Wanita Dewasa Muda Korban Child Sexual Abuse yang Telah Menikah: Studi Fenomenologis - Pingkan C. B. Rumondor (Humaniora, 2012)
Article was aimed to clarify the young adult women’s experience as the victim of Child Sexual Abuse (CSA) who have got married. Qualitative method was applied with phenomenological approach. Analyasis used Interpretative Phenomeniological Analysis (IPA). Data were compiled by semi structured interview having open-ended and non-directive interviews. The research indicates eight themes that can be grouped into two big groups, those are  experince before marriage and experience after marriage. Before marriage experience consists of “It’s just a game”, “ Guilty/self-hatred feeling ”, “Self-Punishment”, “Emotion Focused Coping: Lupain”. After marriage experience expresses “Flashback, ” “Leave me alone”, “Aku butuh cerita” dan “Life must go on”. The research’s findings hopefully will be useful for coubncellors, the spouses of CSA victims, and the other CSA  victims.